Exploration of choroidal vascular changes in juveniles with different degrees of myopia: The application of swept-source optical coherence tomography angiography - Linbo He; Qing Wang; Ziyang Li; Libing Song; Bo Liu; Yuli Yang (Photodiagnosis and Photodynamic Therapy)
Objective: To investigate the vascular characteristic changes in the macular retina and choriocapillaris, as well as the choroidal vascularization of eyes with different degrees of myopia in juveniles using Swept-source Optical Coherence Tomography (SS-OCT), aiming to understand the pathophysiological characteristics of myopic eyes further. Methods: We conducted a retrospective case-control study involving 103 patients (198 eyes) aged 6–17 years who had undergone SS-OCT examination. Based on equivalent spherical power, they were divided into four groups: emmetropia group, low myopia group, moderate myopia group, and high myopia group. The density of superficial capillary plexuses (SCP), choriocapillaris (CC), choroid vessel (CV)layers, and subfoveal choroidal thickness (SFCT) in the macular area were measured using SS-OCT. Multivariate regression analysis was employed to determine the ocular and demographic factors associated with retinal and choroidal blood flow indicators. Results: In the temporal parafoveal area, the superficial capillary plexus (SCP) density was significantly lower in the moderate myopia group compared to the low myopia group (47.27 ± 2.21 vs. 48.51 ± 1.8, p = 0.002). Conversely, subfoveal choroidal vessel (CV) density was substantially higher in highly myopic eyes than in emmetropic eyes (56.98± 3.65 vs. 53.70 ± 4.31, p = 0.023). The multiple linear regression analysis showed that in the area under the fovea, thinner choroidal thickness is associated with higher choroidal vessel density. Specifically, as choroidal thickness decreases, the density of choroidal vessels increases (p = 0.024). Conclusions: For juveniles, with the progression of myopia, the density of retinal superficial blood vessels and choroidal capillaries remains at a relatively stable level, while the choroidal vessel density under the fovea gradually increases. The main cause of changes in choroidal vessel density is the thickness of choroid under the fovea.